Participatory soil and water management - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Informal groups in Mauritania for water and soil conservation were set up and farmers and technicians were given hands-on training in building small dams, dikes, stone contour ridges, semi-circular bunds, terraces and runoff strips.